Bee diversity on urban rooftop food gardens - Riehn, Jordyn K.; Fogel, Nina S.; Hathaway, Jordan N.; Camilo, Gerardo R. (Frontiers in Sustainable Cities, 2023)
Green infrastructure on rooftops in urban areas can enhance important ecosystem services. In addition to mitigating water runoff and regulating building temperatures, green roofs can provide food and nesting resources for wildlife. Rooftop gardens can also be utilized to cultivate food crops, giving them the potential to attenuate instances of food insecurity which are commonplace in many urban areas. Given that many crops depend on bee pollination, it is imperative to characterize the rooftop bee community. Therefore we sampled three urban food roofs near downtown St. Louis, MO during the 2017 and 2018 growing seasons. We found 38 bee species utilizing the rooftop farms. We then compared the rooftop bee communities to those of two nearby ground-level community gardens. The roofs had lower abundances of Bombus species than the ground-level sites while non-native cavity nesters in the genus Megachile were overrepresented. These results indicate that the rooftop bee communities represent a nested subset of the species found at ground level. This has important implications for the management of green roofs for growing crops, as this shift in bee community structure may play a role in determining which crops can be adequately supported with pollination services.